Licenciamento ambiental x conscientização do produtor: situação atual das áreas de produção de arroz em Cachoeira do Sul- RS - Silva, Silvia Marques da; Canto-Dorow, Thais Scotti do (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The Environmental Permit is one of the tools used in order to preservenatural resources for future generations by promoting sustainable managementpractices, especially in agricultural activities that use resources like water, in this study,irrigated rice. Currently, the banking agencies’ requirements for the release of creditfollowing a series of requirements, among them the Environmental Licensing of acreageand Water Management Award. This study aims to evaluate the current situation in theareas of rice production in Cachoeira do Sul in relation to obtaining the licensing andenvironmental conservation. For this, data were collected through interviews, and basedon these findings, held talks with the producers. It can be observed that the majority ofrespondents unaware of the true meaning of Environmental Law, because it compliesLicensing aiming only to agricultural finance. The research demonstrated the need to workwith themes related to environmental preservation, with more direct support and intensive research and extension agencies, so that, together, find solutions for asustainable farm management.